Residents' satisfaction in post-disaster permanent housing: Beneficiaries vs. non-beneficiaries - KamacI-Karahan, Ebru; Kemec, Serkan (Elsevier, 2022)
This paper examines the satisfaction of residents living in post-disaster permanent housing, with particular emphasis on the pre-disaster neighborhood experiences and beneficiary status. Data were obtained by a face-to-face questionnaire survey (N = 171) conducted between January 15 and May 25, 2014, in Sihke post-disaster permanent housing, which was built after the 2011 Van earthquakes in Turkey. Pearson's correlation analysis was used to measure the effect of the relationships between the variables used in the regression analysis. An independent sample t-test was used to assess residents' evaluations of the physical and social settings in the pre-disaster and present resettlement areas, based on their ownership status (beneficiaries versus non beneficiaries). Hierarchical multiple regression analysis was used to determine which factors influenced overall satisfaction with the neighborhood, with beneficiary status, past residential experiences, the social environment, and socio-demographic factors as controlling variables. The preliminary findings show that being a beneficiary, the pre-disaster and current neighborhood environments, and social ties are dimensions and predictors of residents' satisfaction with post-disaster permanent housing in the context of Van, Turkey.
Keywords: Pre-disaster neighborhood experience; Post-disaster permanent housing; Satisfaction; Beneficiary status; Hierarchical multiple regression analysis